1708a Scores predictive for asbestos exposure, malignant mesothelioma and pleural plaque on the basis of comprehensive immunological analysis. (24th April 2018) - Nishimura, Y; Lee, S; Matsuzaki, H; Kumagai-Takei, N; Yoshitome, K; Nakano, T; Kishimoto, T; Otsuki, T
Abstract : Introduction: Our findings about immunological profiles resulted from asbestos exposure and related with malignant mesothelioma (MM) allowed us to think a possibility to construct immunological scoring system to screen mesothelioma and asbestos exposure. Therefore, the present study comprehensively investigated immunological characteristics of plasma and peripheral blood mononuclear cells (PBMC) to obtain the formulae of the scores statistically. Methods: Blood specimens were obtained from 27 healthy volunteers (HV), 29 pleural plaque-positive people (PL) and 30 MM patients. Plasma and PBMC were assayed for cytokines and expression of cell surface molecules on CD4 + (Th), CD8 + (CTL), CD56 + (NK) lymphocytes and monocytes by luminex and flow cytometry. The part of PBMC was sorted into the four cell populations, which were assayed for mRNAs in fresh or after stimulation by realtime-PCR. The results were examined by multiple regression analysis to obtain the formulae of the scores. Results: Both of MM and PL showed decreases in CXCR3 and NKp46 on T and NK cells respectively and increase in granzyme B mRNA in stimulated CTL. IFN-λ and IL-17A in plasma were high in PL, whereas inflammatory cytokines including IL-6 and IP-10 were high in MM. Also, MM showed increase in CTLA-4 on Th cells. The 33 parameters with significant differences were examined by multiple regression analysis. The formulae of scores predictive for MM (M-score), both of MM and PL meaning asbestos exposure (A-score) and PL (P-score) were calculated and composed of the three parameters respectively. Every score showed a good ROC curve with sensitivity and specificity near 0.9. Conclusion: The findings of similarity between PL and MM might reflect alteration caused by inhaled asbestos. The high Treg marker with high inflammatory cytokines might be linked to MM development. Finally, we could obtain the three scores showing good ROC curves, which might be valuable to screen MM and asbestos exposure.